Rediscovery of Apis vechti Maa, 1953: The Saban Honey Bee - Tingek, Salim; Mardan, Makhdzir; Thomas E., Rinderer; Koeniger, Gudrun (EDP Sciences, 1988)
The species Apis Vechti (MAA, 1953) the Sabah honey bee is organized as a valid species. Additional to the description of MAA (1953) species-specific characters associated with the endophallus, hind leg tibial hair of the drone and worker bee fore-wing venation are described.